Warriors of the Pacific, circa 1951-1969 (1951)
Peter Mehlschau, Nipomo, a senior at California State Polytechnic College, and a 'Warrior in Service of the Great Kamehameha pose together after Mehlschau's score of 234 out of a possible 250 helped clinch the trophy for California State Polytechnic College's ROTC branch.The trophy, first presented by the University of Hawaii in 1925, is presented to the college ROTC unit with the highest average M1 rifle score. Competition is among all college units attending ROTC summer camps throughout the United States. Mehlschau was second high man out of 1178 cadets during training at Fort Lewis, Washington. The award previously has been won by the University of Puerto Rico, Ohio University, University of West Virginia, Pennsylvania Military Academy and the University of Hawaii.